Sepsis-induced myocardial depression and takotsubo syndrome. (September 2014) - Y-Hassan, Shams; Settergren, Magnus; Henareh, Loghman
Abstract Background and objectives: Myocardial depression in the setting of sepsis and septic shock is common and has been recognized for a long time. The aim of this study is to find out an association and causal link between sepsis and takotsubo syndrome (TS). Methods: Fifteen cases of TS were studied. Critical review of the literature dealing with sepsis and myocardial depression was done Results: Fifteen cases of sepsis-induced TS are described. Fifty-three per cent of the patients were men. The ages ranged from 39 to 76 years (mean age 60 years). Two-thirds of the patients had ST-elevation myocardial infarction ECG changes. Complications occurred in 80% of the patients. No specific types of sepsis or micro-organisms were associated with the development of TS. Critical review of the sepsis-induced myocardial depression shows that the left ventricular dysfunction, which is reversible within one-to-two weeks, is characterized by segmental ventricular dysfunction, and involvement of the right ventricle in one fourth of cases. These features are also consistent with TS. Conclusions: Sepsis triggers TS, which may be the cause of the majority of cases of sepsis-induced myocardial depression. Acute cardiac sympathetic disruption with noradrenaline spill-over may be the cause of sepsis-induced TS.